PH-potentiometric investigation towards chelating tendencies of p -hydroquinone and phenol iminodiacetate copper(II) complexes - Stylianou, Marios; Keramidas, Anastasios D.; Drouza, Chryssoula (My University, 2010)
Copper ions in the active sites of several proteins/enzymes interact with phenols and quinones, and this interaction is associated to the reactivity of the enzymes. In this study the speciation of the Cu 2+ with iminodiacetic phenolate/hydroquinonate ligands has been examined by pH-potentiometry. The results reveal that the iminodiacetic phenol ligand forms mononuclear complexes with Cu 2+ at acidic and alkaline pHs, and a binuclear O phenolate -bridged complex at pH range from 7 to 8.5. The binucleating hydroquinone ligand forms only 2:1 metal to ligand complexes in solution. The pK values of the protonation of the phenolate oxygen of the two ligands are reduced about 2 units after complexation with the metal ion and are close to the pK values for the copper-interacting tyrosine phenol oxygen in copper enzymes
Keywords: Complexes; Phenol; Proteins; Enzymes; Copper ions; Potentiometry